Perancangan Ulang Rsud Pandega Pangandaran Dengan Pendekatan User-centered-design (ucd) - Siska Aprilia, Dhea; Cardiah, Tita; Murdowo, Djoko (eProceedings of Art & Design, 2024)
Hospitals serve as health service institutions for the community, including the Pandega Pangandaran Regional General Hospital (RSUD) which operates as a healthcare institution for the people of Pangandaran Regency. The background of this research is the patient dissatisfaction due to discomfort caused by the lack of standardization and an unsupportive interior atmosphere for a healing environment at RSUD Pandega Pangandaran. This observation was gathered through on-site surveys and interviews within the hospital premises. The collected data were then analyzed and compared with benchmark studies and precedents to serve as references and comparisons. Utilizing a User-Centered Design approach, this study aims to implement the Healing Space theme, which integrates natural elements and sensory stimuli to create a comfortable environment for patients. This includes both visual and non-visual connections with nature, material connections with nature, and the use of biomorphic forms and patterns. The results of this research are expected to provide interior design recommendations that not only enhance the patient experience but also improve operational efficiency in the hospital context. Keyword: hospital, user centered design, interior ambience